The Effect of Good Corporate Governance, Profitability and Media Disclosure on Corporate Social Responsibility - Gita Andini Saputri; Suyatmin Waskito Adi (Journal of Economics, Business, and Government Challenges, 2022)
This study aims to determine the effect of disclosure of Good Corporate Governance (GCG), profitability, and media disclosure on Corporate Social Responsibility. The population and sample in this study are property and real estate companies listed on the Indonesia Stock Exchange in 2017-2019. The sampling technique in this study used purposive sampling technique. The number of samples in this study were 75 property and estate companies listed on the IDX in 2017-2019. The data analysis technique used in this study is multiple linear regression. The results of this study indicate that managerial ownership has no effect on CSR. Institutional ownership has an effect on CSR. Independent commissioners have no effect on CSR. The size of the board of commissioners has no effect on CSR. Profitability has no effect on CSR. Media disclosure has no effect on CSR.